Studi Sifat Mekanis Baja Karbon Rendah Akibat Perbedaan Holding Time dalam Proses Pack Carburizing Menggunakan Katalis Cangkang Kerang - Edison Effendy; Marselino Matahelumual (Department of Mechanical Engineering, 2025)
This research aims to evaluate the surface hardness improvement of S-35C steel through the pack carburizing process using an eco-friendly catalyst alternative. The use of conventional, toxic Barium Carbonate (BaCO3) is replaced with a bio-energizer derived from marine shell waste, which is rich in natural Calcium Carbonate (CaCO3). The research method utilized was experimental, where steel specimens were completely buried in a media mixture of 60% nani wood charcoal and 40% shell powder. The heating process was conducted at a target temperature of 900°C with holding time variations of 15, 30, and 45 minutes, followed by rapid quenching in SAE 20-50 oil. Hardness testing was performed using a Rockwell (HRC) scale machine. The results indicate that the use of the seashell biocatalyst effectively increased the surface hardness value of the steel. There is a directly proportional relationship between the holding time duration and the hardness improvement. The most optimal hardness value was achieved at a holding time of 45 minutes, showing a net increase of +20.38 units (21.60%) from an initial average of 94.33 units to 114.71 units. A physical deceleration phenomenon in the carbon diffusion rate was also observed as the holding time increased, which strongly aligns with Fick's Second Law of Diffusion. Keyword : pack carburizing, shell waste, hardness, holding time